A bile duct stent broken during repeat pregnancy in a post-liver transplant patient - P. G. Tarazov; A. A. Polikarpov; D. A. Granov; V. V. Borovik (Вестник трансплантологии и искусственных органов)
A young female patient who developed anastomotic biliary stricture following an orthotopic liver transplantation was observed. A self-expandable metallic stent was placed to correct the stricture. At the 8th month of her repeat pregnancy, the stent broke asymptomatically into half. Fortunately, the second childbirth, like the first one, had no complications. Eighteen months later, due to obstruction of fragments by sludge and gallstones, re-stenting was performed with a coated biliary stent. Four years and five months later, recurrent jaundice occurred due to occlusion of the second stent. This was addressed by surgical removal of both stents. Two years after surgery, the bile ducts remain completely patent. We found only two cases in literature on a similar extremely rare biliary stenting complication. It has been suggested that stent deformation may be related to pregnancy. The feasibility of using stenting in benign biliary strictures in some clinical situations is discussed.